Solvent dependent reactivity: solvent activation vs. solvent coordination in alkylphosphane iron complexes - Heinemann, Frank Wilhelm; et al. (Dalton Transactions, 2006)
The pyridine-derived tetrapodal tetraphosphane C5H3N[CMe(CH2PMe2)(2)](2) (1) is susceptible to selective protonolysis of a phosphorus-carbon bond in the presence of iron(II) salts. Water produces dimethylphosphinic acid, Me2POH, and protonates the anionic remainder of the tetraphosphane. The resulting iron(II) complexes 2 and 3 (tetrafluoroborate and perchlorate salts, respectively) contain the residual chelate ligand in which a methyl group, derived from the ligand skeleton, is in agostic interaction with the metal centre, and in which Me2POH, unavailable in the free state owing to rapid tautomerisation, is metal-coordinated and thus stabilised. Full NMR details are presented, including P-31 simulations. The reactivity towards alcohols is similar (compounds 4, 5), and has been studied using deuterium labels (NMR). P-C bond cleavage may be suppressed only if all protic agents are rigorously excluded, as in the reaction of 1 with Fe(SO3CF3)(2)center dot 2CH(3)CN in acetonitrile solution, which produces the complex [(1)Fe(NCMe)](SO3CF3)(2) (6). In it, the ligand acts as an NP4 coordination cap but is severely distorted from square-pyramidal geometry. The reaction of 1 with anhydrous ferrous bromide, FeBr2, in methanol again produces a dimethylphosphinic acid ester ligand, but the complex (7) now contains ferric iron coordinated by a carbanionic residual chelate ligand, implicating H+ as the oxidising agent under these conditions. Full spectroscopic and X-ray structural details are presented for all compounds.